Large group differences in binaural sensitivity are represented in preattentive responses from auditory cortex - Lertpoompunya A. (2023)
Correlated sounds presented to two ears are perceived as compact and centrally lateralized, whereas decorrelation between ears leads to intracranial image widening. Though most listeners have fine resolution for perceptual changes in interaural correlation (IAC), some investigators have reported large variability in IAC thresholds, and some normal-hearing listeners even exhibit seemingly debilitating IAC thresholds. It is unknown whether or not this variability across individuals and outlier manifestations are a product of task difficulty, poor training, or a neural deficit in the binaural auditory system. The purpose of this study was first to identify listeners with normal and abnormal IAC resolution, second to evaluate the neural responses elicited by IAC changes, and third to use a well-established model of binaural processing to determine a potential explanation for observed individual variability. Nineteen subjects were enrolled in the study, eight of whom were identified as poor performers in the IACthreshold task. Global scalp responses (N1 and P2 amplitudes of an auditory change complex) in the individuals with poor IAC behavioral thresholds were significantly smaller than for listeners with better IAC resolution. Source-localized evoked responses confirmed this group effect in multiple subdivisions of the auditory cortex, including Heschl's gyrus, planum temporale, and the temporal sulcus. In combination with binaural modeling results, this study provides objective electrophysiological evidence of a binaural processing deficit linked to internal noise, that corresponds to very poor IAC thresholds in listeners that otherwise have normal audiometric profiles and lack spatial hearing complaints.